Clinical outcomes and predictors of mortality in COVID-19 patients admitted to a High Dependency Unit in Pakistan-a cross-sectional study - Fatima, Samar; Shamim, Sara; Ejaz, Taymmia (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the outcomes and predictors of in-hospital mortality of patients admitted to high-dependency unit with coronavirus disease 2019 infection. Method: The retrospective study was conducted at a tertiary care hospital in Karachi, and comprised data of adult coronavirus disease 2019 patients of either gender admitted to the high dependency unit from March 1 to June 30, 2020. Outcomes were categorised as patients ‘recovered without deterioration’, ‘deteriorated but survived’, and ‘deteriorated but expired’. Data was analysed using SPSS 22. Results: Of the 525 patients with confirmed infection, 245(46.6%) were admitted to the high dependency unit. Leaving out 38(15.5%) cases with missing data, 207(84.5%) cases formed the study sample; 156(75.4%) males and 51(24.6%) females. The overall mean age was 56.9±14years (range: 24-86 years). The most common comorbid condition was hypertension 105(50.7%), and the most common reason for critical care was hypoxic respiratory failure 199(96.1%). Of the total, 153(74%) patients recovered, 31(15%) deteriorated, and mortality was the outcome in 23(11%). There was no significant effect of drug treatment on mortality (p>0.05). Age, multimorbidity and high D-Dimer level were significantly associated with disease progression and mortality (p<0.05). Conclusion: Mortality was high among coronavirus disease 2019 patients who were older and had multimorbidity. Key Words: COVID-19, In-hospital mortality, Multimorbidity, SARS-CoV-2 infection, Critical care outcomes.